Separation and Purification of AFB1-degrading Enzyme by Tannin Adsorption-Poly (Ethylene Glycol) Desorption Method - PENG Wei-wei; LI Ji-ying; WANG Jia-xing; XIE Yan-li; LI Xiao (Liang you shipin ke-ji)
Based on the screening of Aspergillus terreus HNGD-TM15 from rosemary soil that can efficiently degrade AFB1 in our laboratory, AFB1-degrading enzymes in the fermentation broth of Aspergillus terreus HNGD-TM15 were isolated and purified by tannin adsorption and desorption of Polyethylene Glycol 6000 (PEG 6000) under optimal fermentation conditions. As the tannin concentration increased from 2 mg/mL to 34 mg/mL, the AFB1 degradation rate of the supernatant decreased from 85.54% to 9.13%, suggesting that the AFB1-degrading enzyme was adsorbed onto the tannin. To desorb the enzyme from the tannin-AFB1-degrading enzyme complex, PEG 6000 was employed as a desorbent. Optimal desorption occurred with a 12 mg/mL PEG solution, successfully desorbing the complex at a 24 mg/mL tannin concentration. The purified enzyme solution exhibited an AFB1 degradation rate of 79.91%, and the optimal adsorption and desorption time was 60 minutes. The highest enzyme purification efficiency was achieved when the ratio of tannin concentration to PEG concentration was 2∶1. This study demonstrates that tannin adsorption coupled with PEG 6000 desorption is a safe and effective method for the isolation and purification of AFB1-degrading enzymes, providing a promising strategy for enzyme purification in the fields of food safety and biopharmaceuticals.